PEMBELAJARAN MENULIS CERITA RAKYAT (HIKAYAT) MENGGUNAKAN MEDIA POP UP - Alni Dwi Septiani (IKIP Siliwangi, 2020)
This study aims to increase students' interest in learning in class X MIPA 2 SMAN 1 Cipongkor in literary material, namely folklore (saga) using pop up media, and to help students describe the structure of the story such as the background so that it can be better understood by readers using pop up media. This research method uses qualitative descriptions which aim to make natural descriptions of objects accurately. The data collection technique used during the research was test technique. The test aims to be a measuring tool for students' learning success in writing folk tales (saga) using pop up media. The results showed the students who scored on the initial test with an average score of 43 and the final test with an average value of 77.88. Thus, learning to write folk tales (saga) using pop media has increased very well.